Cost of antibiotics in medical intensive care. (June 2022) - Ismail, D.
Summary: Background: Intensive care units are a prime target for monitoring antibiotic consumption and conducting pharmacoeconomic studies because of their considerable antibiotic use. Aim: To evaluate the consumption and cost of antibiotics globally, per family, and for nosocomial and multidrug-resistant infections. Methods: This is a monocentric, retrospective, and observational study spanning one year (January 1 st, 2018, to December 31 st, 2018), and covering all patients hospitalized in the medical intensive care unit of Ibn Rochd University Hospital of Casablanca in Morocco. Findings: The global annual consumption of antibiotics accounted for 1410.21 defined daily doses (DDD) per 1000 bed-days from which β-lactams were the most consumed (768.95 DDD per 1000 bed-days). Community-acquired infections resulted in annual antibiotic consumption of 1340.82 vs 2483.69 g DDD for nosocomial infections. Multidrug-resistant infections resulted in annual consumption of 737.5 g DDD (52.2%). The global cost of prescribed antibiotics amounted to US$118, 224.32. The consumption of β-lactams (38%) and fluoroquinolones (21%) combined cost ∼60% of the total budget. The cost spent on antibiotics for the treatment of nosocomial infections was US$57, 544.11 vs 60, 859.41 for the treatment of community-acquired infections. The cost of antibiotics prescribed for the treatment of multidrug-resistant infections reached US$47, 744.14. Conclusion: This study made it possible to identify several aspects of misuse and overconsumption which allowed estimating certain expenses that could be entirely avoidable. As a result, this evaluation would be the first step towards the rationalization of antibiotic use.